2019
DOI: 10.1002/nau.24227
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of Twitter activity on #Incontinence

Abstract: Aim: The aim of this study is comprehensive analysis of the Twitter activity on #Incontinence.Material and Methods: The following six functional-urology hashtags on Twitter were analyzed from 2015 to 2018 to gain a comprehensive insight into the topic: #Incontinence, #InterstitialCystitis, #OAB, #FPMRS, #BPH, and #UroBPH. For the Twitter analysis, Symplur Signals was used, which is a health care social media analytics tool.Results: In total 191 383 tweets by 54 094 users in 2015 through 2018 were analyzed. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This Twitter campaign was unique given the interdisciplinary nature of subject, on the interface of computer science, engineering, and medical communities. Previous literature surrounding the use of hashtags in healthcare-associated content amplification tended to pertain to a single community (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Several methodological distinctions are also apparent within our analysis.…”
Section: Summary Cross-evaluation With Contemporary Literaturementioning
confidence: 91%
See 1 more Smart Citation
“…This Twitter campaign was unique given the interdisciplinary nature of subject, on the interface of computer science, engineering, and medical communities. Previous literature surrounding the use of hashtags in healthcare-associated content amplification tended to pertain to a single community (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Several methodological distinctions are also apparent within our analysis.…”
Section: Summary Cross-evaluation With Contemporary Literaturementioning
confidence: 91%
“…Several studies have demonstrated hashtags' utility in amplifying content associated with various topics and events. The inclusion of hashtags in tweets facilitated the promotion of disease-specific tweets (12)(13)(14)(15), Twitter-based chats and journal clubs (16)(17)(18)(19), and meeting or conferencerelated content (20)(21)(22)(23)(24)(25)(26)(27)(28). Hashtags have also been previously demonstrated as an effective tool for content-specific education (13,29).…”
Section: Introductionmentioning
confidence: 99%
“…Engagement with the conversation about gene editing can be an indicator of interaction among the social system as well as approval of or agreement with the message (Grabbert et al, 2019;Kee et al, 2016;Rogers, 2003). Both are goals among communicators who desire to create content that fosters conversation and encourages feedback from the audience.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…External to Meltwater's reporting, the proportion of retweets to original tweets was calculated as an indicator of interaction over the entire search (Grabbert et al, 2019). Of the 13,189 tweets collected, 7,022 (53.2%) were retweets, indicating high interaction among accounts participating in the conversation about gene editing in agriculture (Grabbert et al, 2019). The top 10 Twitter posts in terms of engagement are presented in Table 3.…”
Section: Figurementioning
confidence: 99%
“…Hashtags, which were mentioned above as one of the commonly used tweet components, are designed as keyword-terms (usually thematically related to the content of the tweet) that are missing spaces (in case the term consists of several words) and have a hash sign (#) in front (particular example: #NaturalProducts). Hashtags afford tagging and thematic grouping of tweets and hashtag analysis has been widely used as a research tool that allows different quantifications (Cheung et al, 2018;Gardhouse et al, 2017;Grabbert et al, 2019;Kudchadkar and Carroll, 2020). In this context, relevant visibility parameters associated with tweets that could be analyzed, include retweets (re-shares) and impressions (views).…”
Section: Twitter As a Tool For Science Communication And Networkingmentioning
confidence: 99%